A newly-constructed hydrolytically stable Co(ii) coordination polymer showing dual responsive fluorescence sensing of pH and Cu2+. Issue 24 (4th June 2021) - Yan, Min; Zhu, Peizhi; Yang, Shengyang; Kong, Wei-Jian; Wang, Jian; Zhang, Kou-Lin
Abstract : A novel CP (1 ), showing distinct dual responsive fluorescence sensing of pH in three continuous stages as well as efficient and selective sensing of Cu 2+ . Abstract : Fluorescent chemosensors based on coordination polymers (CPs) have received particular attention in monitoring the pH values and appropriate analytes in environmental and biological systems owing to their extreme superiorities. Herein, a novel solvent-dependent fluorescent Co(ii )-CP, [Co(asba)(2-mmzm)(H2 O)2 ]·3H2 O (1 ), was obtained through the assembly between Co 2+ and 2-amino-4-sulfobenzoic acid (H2 asba) in the presence of the flexible hydrophobic ligand 1, 4-bis[(2-methyl-1 H -imidazol-1-yl)methyl]benzene (2-mmzm). 1 is a 1D coordination polymer, which is further linked by a 1D hydrogen-bonded tape into a 3D supramolecular network. 1 shows high hydrolytic stability as well as strong acidic and basic resistance. Remarkably, 1 is a quite rare example that shows dual responsive fluorescence sensing of pH and Cu 2+ . 1 shows distinct sensing behavior toward pH with interesting different sensing mechanisms in three continuous pH ranges. Moreover, 1 demonstrates high accuracy in determining the pH of artificial gastric juices. 1 could also sensitively and selectively sense Cu 2+ ions over a number of interfering metal ions. The limit of detection (LOD) for Cu 2+ reaches the 2.4 μM level.